THE EFFECT OF KANGAROO METHOD ON IMPROVEMENT BODY WEIGHT ON LOW BIRTH WEIGHT - Yeni Riskawati; Martono Tri Utomo; Pudji Lestari (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: In Indonesia the Neonatal mortality rate was 15 infants per 1000 births and in Surabaya in 2018 LBW deaths were 50 per 1000 live births, while in Haji General Hospital the LBW deaths were 12 babies in 1 year. Kangaroo care was the most effective way to meet the basic needs of LBW. Babies with 1500-2500 grams body weight either due to prematurity or small pregnancy period will lose weight ranging from 10-15% in 7 days of life. To overcome the problem Kangaroo care method4 component aims to promote weight loss, maintain body temperature remains stable and facilitate breastfeeding Methods: The method of this study was observational analytic with the design of the study cohort. Total sample of 40 LBW with sampling techniques using Sequential Sampling in the period August-October period 2019. Variabel was free kangaroo care method  given 1-2 times a day with a duration of more than 120 minutes. The dependent variable was increased in body weight carried out 3x the measurement. Results: The results of the study using paired T test showed an increase in body weight, namely 1) the first measurement of 31.82 grams for 3 days with p = 0.037, 2) the second measurement increased by 227.15 for 7 days, with p = 0,000, 3) the third measurement was 258.97 with p = 0,000. The conclusion: of the studied, that there were a significant difference between the kangaroo method treatments for weight gain in LBW in the NICU Room Haji Hospital Surabaya